2022
DOI: 10.3389/fneur.2022.865462
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive and Mood Profiles Among Patients With Stiff Person Syndrome Spectrum Disorders

Abstract: An emerging body of evidence suggests that changes in cognitive and emotional function are common aspects of stiff person spectrum disorders (SPSD). We sought to examine the pattern of cognitive impairment and psychiatric symptoms in SPSD.MethodsA retrospective review of medical records was conducted for patients seen at the Johns Hopkins Stiff Person Syndrome (SPS) center from 1997 to January 1st, 2020. Individuals who had received formal cognitive testing as part of routine clinical care for patient-reported… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
0
4
1
Order By: Relevance
“…However, our findings contrast with an older study that reported that patients with SPS had phobic neurosis, believing that their fears are unrealistic 102 . A 2022 study, based on a retrospective chart review, concluded that patients with SPS spectrum disorders have impaired verbal learning and recall memory, verbal fluency, attention, and processing speed 103 . This study should also be viewed with caution because most of these patients did not have pure SPS; they had other comorbidities or neurologic disorders and had been receiving combinations of benzodiazepines, antidepressants, antispasmodic medications, antiseizure medication, and opioids.…”
Section: Therapeutic Strategies In Stiff Person Syndrome Spectrum Dis...contrasting
confidence: 98%
“…However, our findings contrast with an older study that reported that patients with SPS had phobic neurosis, believing that their fears are unrealistic 102 . A 2022 study, based on a retrospective chart review, concluded that patients with SPS spectrum disorders have impaired verbal learning and recall memory, verbal fluency, attention, and processing speed 103 . This study should also be viewed with caution because most of these patients did not have pure SPS; they had other comorbidities or neurologic disorders and had been receiving combinations of benzodiazepines, antidepressants, antispasmodic medications, antiseizure medication, and opioids.…”
Section: Therapeutic Strategies In Stiff Person Syndrome Spectrum Dis...contrasting
confidence: 98%
“…Along the same lines, use of increased exteroceptive reflex on EMG may assist as well in diagnosis [ 19 ]. In addition, there were other associated symptoms that have been less well recognized, but still frequently reported and identified, including gastrointestinal symptoms [ 20 ], cognitive dysfunction [ 21 ], mood disorders, and even photosensitivity [ 22 ]. These less recognized symptoms are interesting and may suggest SPSD as a more multi-system disorder.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to identify these under-recognized symptoms of SPSD to allow for monitoring of disease and treatment of associated symptoms. There is some literature suggesting high incidence of and potentially an increased risk of psychiatric comorbidities in SPS [ 21 , 23 , 24 ]. Recognizing the frequent confounding factors of psychiatric co-morbidities is important as to not mis-attribute such symptoms to psychiatric or psychogenic processes [ 23 , 25 , 26 ] and also to improve the identification of these co-morbid conditions which need treatment.…”
Section: Discussionmentioning
confidence: 99%
“…16 Considering that low GABA has been connected to anxiety disorders, this observation is important, and on this basis, we need to reassure the patients from the outset that if the disease improves with prompt initiation of combined therapies, their phobias will also improve, a conclusion supported by the controlled trial with IVIg, which, as discussed later, demonstrated that when the physical signs of stiffness improved, so did the phobias. A recent report that SPS-SD patients have impaired verbal learning and recall fluency, attention, and processing speed 33 should be viewed with caution because it was based on a retrospective chart review of patients with SPS-SD, most of which did not have pure SPS but other comorbidities or neurologic impairments, for which they have been receiving variable combinations of benzodiazepines, antidepressants, antispasmodics, antiepileptics, and opioids.…”
Section: Role Of Supportive Psychotherapiesmentioning
confidence: 99%